Comparison of transcatheter arterial chemoembolization combined with radiofrequency ablation or microwave ablation for the treatment of unresectable hepatocellular carcinoma: a systemic review and meta-analysis. (1st January 2020) - Zhao, Jiani; Wu, Jianxin; He, Mengyu; Cao, Menghao; Lei, Jun; Luo, Hongliang; Yi, Fengming; Ding, Jingli; Wei, Yiping; Zhang, Wenxiong
Abstract: Background: Transcatheter arterial chemoembolization (TACE), radiofrequency ablation (RFA), and microwave ablation (MWA) are regarded as effective therapies for treating unresectable hepatocellular carcinoma (HCC). We conducted this study to compare the efficiency and safety of TACE combined with RFA (TR group) or MWA (TM group). Method: PubMed, the Cochrane Library, Ovid Medline, Web of Science, Scopus, Embase, ScienceDirect, and Google Scholar were searched. The primary endpoints were overall survival (OS), progression-free survival (PFS), response rates, and complications. Result: Eight cohort studies and one randomized controlled trial were included. The TM group had better OS (Hazard ratio [HR]: 1.55; 95% confidence interval [CI]: 1.09–2.21, p  = 0.01) and a better 2- and 3-year OS rate, 24-month PFS rate (Risk ratio [RR]: 0.67; 95% CI: 0.46–0.96, p  = 0.03), and complete response rate (RR: 0.87; 95% CI: 0.79–0.96, p  = 0.003) than the TR group. Furthermore, the TM and TR groups did not show significant differences in PFS, the disease control rate or complications. The advantage of TM was mainly reflected in younger patients (50–60 years old) compared with patients aged 60–70 years, as well as in patients with larger tumors (≥3 cm) compared with patients with tumors <3 cm. Moreover, patients treated with conventional TACE (cTACE) in the TM group showed longer OS, while patients treated with drug-eluting bead transarterial chemoembolization (DEB-TACE) in the TR group showed a higher overall response rate. Conclusion: TM seems to be a more effective therapy than TR for unresectable HCC, with better survival and similar safety.